Penyuluhan Legalitas UMKM Dalam Rangka Peningkatan Kualitas Produk Berbasis Ekonomi Kreatif - Diva Klandy Lumansik; Aufa Izzudin Baihaqi (Nanggroe: Jurnal Pengabdian Cendikia, 2023)
In facing competition, MSMEs are often faced with challenges in maintaining and improving the quality of their products. One of the challenges faced by MSMEs is legality, in this case the Business Identification Number (NIB). Legality is one of the challenges for MSME actors to improve the quality of their products. One of the important factors in improving the quality of MSME products is legality. Many MSMEs in Menur Pumungan Village still do not have a Business Identification Number (NIB) even though they will get many benefits if they have a Business Identification Number (NIB). There are still many who do not know the importance of business legality and think that making a Business Identification Number (NIB) takes a long time and is complicated. This counseling aims to foster an entrepreneurial mindset and raise awareness on the importance of business legality in an effort to improve the quality of creative economy-based products needed in their business activities and help them to obtain a Business Identification Number (NIB) for their business. The impact on MSME players who take part in the counseling and assistance of the Business Identification Number (NIB) is that they can take the right steps to protect their business, obtain funding, optimize the production process and improve the quality of the products they sell. Not only that, it can also contribute to increasing the competitiveness of MSMEs in domestic and international markets. Businesses that have legality can provide and increase confidence to consumers about the quality and authenticity of their products.